The relationship between self‐Image and social anxiety in adolescence. Issue 2 (22nd July 2014) - Di Blasi, Maria; Cavani, Paola; Pavia, Laura; Lo Baido, Rosa; La Grutta, Sabina; Schimmenti, Adriano
<x xml:space="preserve">Abstract</x> Background Self‐image is the subjective perception about one's own self, body, mental functioning, social attitudes, and adjustment in different aspects of life. Research has linked negative self‐image with a number of problem behaviors and psychiatric symptoms in adolescence; however, studies of the relationship between self‐image and anxiety disorders are still scarce. Method This study involved a community sample of 1305 high‐school students (51.4% female) who ranged in age from 14 to 19 years old. They completed self‐report measures of self‐image and social anxiety disorder (SAD). Results A quarter of the students reported high levels of social anxiety. Statistical analyses showed significant differences between these students and the other students in all the self‐image subscales. Several dimensions of impaired self‐image (emotional tone, social attitudes, vocational and educational goals, family relationships, external mastery, and psychological health) were associated with high levels of social anxiety, with some gender differences underpinning these relationships. Conclusions Clinicians treating SAD in youth may wish to consider that a negative self‐image may play a critical role in the onset and retention of social anxiety symptoms.